2019
DOI: 10.1002/jgc4.1122
|View full text |Cite
|
Sign up to set email alerts
|

Current genetic counseling practice in the United States following positive non‐invasive prenatal testing for sex chromosome abnormalities

Abstract: The purpose of this study was to describe current genetic counseling practice in the United States following a non‐invasive prenatal testing (NIPT) result positive for a sex chromosome abnormality (SCA). Screening for SCAs can be confounded by confined placental mosaicism, natural loss of the X chromosome from maternal cells during aging, and undiagnosed maternal SCA or copy number variant (CNV). Furthermore, with the exception of 45,X, individuals with SCAs usually have no ultrasound or postnatal findings. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…32 Once the pregnancies were confirmed as SCAs by prenatal diagnosis, genetic counselling information that is accurate, updated and relevant should be provided to the pregnant woman and her family. 33,34 Genetic counselling should include the SCA prognosis, early intervention or any expected treatment research progress so that the pregnant women and their families could obtain sufficient information to help them make the best decision. Therefore, genetic counselling physicians However, recent research has shown that after conduct SCAs prenatal diagnosis, the baby can allow earlier intervention and care as well as not miss the optimal timing of early medical intervention and education.…”
Section: Discussionmentioning
confidence: 99%
“…32 Once the pregnancies were confirmed as SCAs by prenatal diagnosis, genetic counselling information that is accurate, updated and relevant should be provided to the pregnant woman and her family. 33,34 Genetic counselling should include the SCA prognosis, early intervention or any expected treatment research progress so that the pregnant women and their families could obtain sufficient information to help them make the best decision. Therefore, genetic counselling physicians However, recent research has shown that after conduct SCAs prenatal diagnosis, the baby can allow earlier intervention and care as well as not miss the optimal timing of early medical intervention and education.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, up to 50% women with 45,X were mosaic and the incidence of SCAs may be higher than the estimation [17]. However, SCAs screening remains controversial as it may lead to an increase in sex selection and NIPT would contribute to screening for relatively benign conditions (e.g., 47,XXX and 47,XYY) which are still difficult for genetic counseling and parental decisions [17,26]. On this basis, it is vital to inform pregnant women and family members about the accuracy of cfDNA testing in the context of SCAs.…”
Section: Discussionmentioning
confidence: 75%
“…SCAs are the most frequent aneuploidy in human beings with an estimated prevalence of over 1/500 [25]. In a previous study, up to 50% women with 45,X were mosaic and the incidence of SCAs may be higher than the estimation [17]. However, SCAs screening remains controversial as it may lead to an increase in sex selection and NIPT would contribute to screening for relatively benign conditions (e.g., 47,XXX and 47,XYY) which are still difficult for genetic counseling and parental decisions [17,26].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Non-invasive prenatal testing (NIPT) shouldn't be recommended to them because of the maternal mosaicism [20][21][22].…”
Section: Genetic Consultmentioning
confidence: 99%